A real time optoelectronic device as an adjunct to the Pap smear for cervical screening: A multicenter evaluation. Issue 6 (1st October 2003) - Singer, A.; Coppleson, M.; Canfell, K.; Skladnev, V.; Mackellar, G.; Pisal, N.; Deery, A.
Abstract : We report on the results from a multicenter trial for a real time optoelectronic device as an adjunct to the Pap smear for cervical screening. TruScreen (Polartechnics Limited, Sydney, Australia) is an automated device which measures the response to optical and electrical stimulation of the cervix and returns a screening result in real time. Analysis was performed on a group of 651 subjects recruited at 10 centers. Cytology and histology analyses were performed by centralized laboratories, with the cytology classification performed according to the Bethesda 2001 system. The sensitivities for histologically confirmed CIN 2/3 lesions by TruScreen, Pap, and TruScreen/Pap combined were 70% (95% CI: 67–74), 69% (CI: 65–72), and 93% (CI: 91–95), respectively. For histologically reported CIN 1, the sensitivities of the TruScreen, Pap, and combined test were 67% (CI: 63–70), 45% (CI: 41–49), and 87% (CI: 84–89). The improvement in sensitivity for the combined test compared to the Pap smear alone was significant ( P = 0.002). Because TruScreen and cytology detect partly different but overlapping groups of CIN cases, the adjunctive combination provides very high CIN detection rates.